Meeting complex needs: young people with HIV in London. Issue 3 (23rd September 2012) - Hughes, A; Hope, RL; Nwokolo, N; Ward, B; Jones, R; Von Schweitzer, M; Boag, F
Abstract : Objectives: The aim of the study was to examine the service use and characteristics of young people diagnosed with HIV infection aged under 25 years in order to design appropriate services. Methods: A retrospective review of medical records of all individuals diagnosed as HIV positive aged under 25 years at Chelsea and Westminster Hospital, London, UK was carried out. The Health Protection Agency traced all individuals who had been lost to follow‐up. We collected demographic, clinical, social and behavioural data. Results: Of the 100 individuals diagnosed as HIV positive aged <25 years, 91% acquired HIV sexually; the median age at diagnosis was 21 years. Fifty‐nine per cent were born outside the UK. Of 91 individuals diagnosed in the UK, 20% were diagnosed outside genitourinary medicine. Almost half had tested HIV negative a median of 13 months previously. At HIV diagnosis, 26% had a concurrent sexually transmitted infection; thereafter 34% had a documented risk of HIV transmission. The prevalence of psychiatric comorbidity was high (23%). Cervical screening rates were low; of nine women screened, five required treatment for cervical or vulval neoplasia. One fifth of the cohort were lost to follow‐up a median 6 months from diagnosis. Conclusions: Young people with sexually acquired HIV infection have complex medical and psychosocial needs and many disengage from health services. Current services are not meeting the needs of these young people. Specialist young people's clinics may improve standards of care for this vulnerable group.